2017
DOI: 10.1016/j.redox.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Fetal hemoglobin is much less prone to DNA cleavage compared to the adult protein

Abstract: Hemoglobin (Hb) is well protected inside the red blood cells (RBCs). Upon hemolysis and when free in circulation, Hb can be involved in a range of radical generating reactions and may thereby attack several different biomolecules. In this study, we have examined the potential damaging effects of cell-free Hb on plasmid DNA (pDNA). Hb induced cleavage of supercoiled pDNA (sc pDNA) which was proportional to the concentration of Hb applied. Almost 70% of sc pDNA was converted to open circular or linear DNA using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…However, electron transfer can be mediated via other residues. For instance, the more distant α19 can interact via αTyr24, located 16.5 Å from the α-heme iron and 7.9 Å from α19, as proposed previously as a route of electron transfer [22] .…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…However, electron transfer can be mediated via other residues. For instance, the more distant α19 can interact via αTyr24, located 16.5 Å from the α-heme iron and 7.9 Å from α19, as proposed previously as a route of electron transfer [22] .…”
Section: Discussionmentioning
confidence: 55%
“…Cell-free Hb is used as the principal component but the oxidative reactions of the protein present problems that must be resolved. In this study, the focus has been on protein engineering of HbF as a substitute for HbA due to its reported potential advantages as a starting material for oxygen therapeutic development [12] , [21] , [22] . However, even though αA19C appears to be a promising mutation in terms of providing oxidative stability of HbF, there could also be other possible positions where cysteine residues can be introduced in the protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lower oxygen affinity of adult Hb does not seem to influence fetal metabolism when Hb levels are normal; nevertheless, during moderate or severe anaemia, it has been shown that cord blood samples containing higher levels of adult Hb have also a lower pH and higher base deficit . Notably, as compared to adult Hb, fetal Hb has a significantly greater capacity to generate nitric oxide (which plays an important role in regulating vascular tone and blood flow) , is oxidatively more stable and is less prone to the DNA cleavage activity .…”
Section: The Rationale For Using Umbilical Blood To Transfuse Pretermmentioning
confidence: 94%